MODERN POSSIBILITIES OF THERAPY WITH INHIBITORS OF CONTROL POINTS IN METASTATIC UROTHELIAL CANCER - R. A. Gafanov; S. V. Garmash; I. B. Kravtsov; S. V. Fastovets (Исследования и практика в медицине, 2018)
For a long time, chemotherapy remained the main treatment option for metastatic urothelial carcinoma (mUC). Over the past year, there have been revolutionary changes associated with the approval of five new drugs aimed at blocking the interaction between the surface protein of T-lymphocytes PD-1 and its ligands PD-L1 and PD-L2, resulting in the activation of the immune response. It is noteworthy that the anti-PD-1 antibody pembrolizumab demonstrated an increase in overall survival relative to chemotherapy in a randomized phase III trial in the second line with mUC. Based on this level 1 evidence pembrolizumab was approved by the US Food and Drug Administration (FDA). Nivolumab (antibody PD-1) also demonstrated an increase in overall survival compared to historical control and was approved by FDA. Likewise, antibodies targeting PD-L1, including atezolizumab, durvalumab and avelumab, received accelerated approval from the FDA as the second line of treatment for mUC. Some of these agents are approved in the first line by the results of phase II study (atezolizumab and pembolizumab received accelerated approval for first-line treatment in patients not receiving cisplatin). Despite these many endorsements, clinical development of new biomarkers for selection of patients, who can get maximum advantages of immunotherapy and also for development the optimal therapy sequencing still are biggest and critical question for future investigation. The clinical introduction of biomarkers to determine optimal treatment of patients remains extremely important.